PRODUCTION AND ECONOMIC SPECIFICITIES IN GROWING OF DIFFERENT GARLIC VARIETIES - Totić, Ibrahim; Čanak, Stevan (Economics of Agriculture, 2014)
Importance of garlic is enormous for both human health and cookery. Garlic is a crop whose production does not endanger the agro-system and the eco-system, which is of special significance for organic food production. Considering that growing garlic is based on the application of agro-ecological and agro-economic principles, this paper describes the soil preparation process for planting, planting technology, application of agro-technological measures. It also gives an account of the basic characteristics of the planting material, its extraction and storage. The subject of research of this paper is to determine yield of different garlic types on two different locations in Serbia. It also aims to determine costs and calculations based on variable costs, as well as to compare economic results of production of different garlic types on family-own small-scale farms.